Pelatihan Riset Akuntansi Dengan Smart PLS Bagi Mahasiswa Doktoral Akuntansi Universitas Trisakti - Tambun, Sihar; Sitorus, Riris Rotua (CV. Ulil Albab Corp, 2024)
The aim of this community service activity is to educate Trisakti University accounting doctoral students about how to process research data in the field of accounting using Smart PLS software. In particular, the run data technique is based on structural equation modeling with an intervening model and a moderating model. There are two methods used, the first is the lecture method for explaining concepts and theories. Second, the practical method of data processing using Zoom Meeting media. The number of participants who filled out the evaluation form was 24 participants, namely participants who had never studied Smart PLS before. The evaluation instrument used was questions on Google forms related to understanding the training material. The evaluation results showed that there was an increase in the participants' abilities. First, increasing the ability to prepare Excel CSV data and data input capabilities, as well as the ability to draw research models. Second, increasing the ability to carry out validity and reliability tests, as well as the reduction process for invalid questions. Third, increasing the ability to evaluate r square and goodness of fit, as well as compiling structural equations. Fourth, the ability to test intervening SEM models, as well as interpretation of direct effects and indirect effects. Fifth, the ability to test the SEM moderating model, as well as interpret the moderating effect.